2012
DOI: 10.1177/0731684412454461
|View full text |Cite
|
Sign up to set email alerts
|

Prediction on macroscopic elastic properties of interphase-contained long-fiber-reinforced composites and multiple nonlinear regression analysis

Abstract: A convenient method to predict the macroscopic elastic performance of composite containing interphase was developed in this paper based on a new modified random sequential adsorption method and multiple nonlinear regression analysis. First, a three-phase micromechanical model with randomly distributed fibers was established with a new modified random sequential adsorption method named the Moving Window Method. Second, the macroscopic elastic behaviors of T300/914C were predicted based on micromechanical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It is observed that the longitudinal and transverse moduli (E11 and E22) and strengths (S11 and S22) of composites enhance with increasing V i ; however, the E11 improvement is noticeably higher. Increase in E11 and E22 values with increasing interphase content in RVE were also reported by Liu et al 27 Moreover, the FE simulations demonstrate that the presence of glass fiber along loading direction makes composite stiffer where E11 is noticeably larger than E22. The aforementioned result of modulus is consistent with experimental results of Mortazavian and Fatemi.…”
Section: Tensile Behavior Of Fibrous Compositesupporting
confidence: 80%
“…It is observed that the longitudinal and transverse moduli (E11 and E22) and strengths (S11 and S22) of composites enhance with increasing V i ; however, the E11 improvement is noticeably higher. Increase in E11 and E22 values with increasing interphase content in RVE were also reported by Liu et al 27 Moreover, the FE simulations demonstrate that the presence of glass fiber along loading direction makes composite stiffer where E11 is noticeably larger than E22. The aforementioned result of modulus is consistent with experimental results of Mortazavian and Fatemi.…”
Section: Tensile Behavior Of Fibrous Compositesupporting
confidence: 80%
“…In Abaqus, the constitutive response of cohesive elements is defined in terms of traction versus separation and Zhang et al gave the interfacial stiffness K i (that directly relates the nominal stress to the displacement) of similar material system. Liu et al obtained the reasonable interfacial properties by averaging properties of matrix and fiber from an exponential gradient distribution, which could be utilized to calculate the CTE of interface. Therefore, mechanical properties for this verification are listed in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…This region has been reported to have thickness between 30 nm and 1 m for the case of GFRPs [10,11] and can be tailored by acting upon the thickness of fibre coatings [12]. Modelling such interphases can be necessary to improve the accuracy of simulations and several authors have studied the effects of the interphase on the stiffness and damping of FRPs with circular fibres by analysing the response of periodic unit cells based on square or hexagonal arrangement of fibres ( [13][14][15][16][17][18]) and, for case of elastic properties, analysing the response of random RVEs [19][20][21].…”
Section: Introductionmentioning
confidence: 99%